Identifying critical factors influencing the safety of Chinese subway construction projects. Issue 7 (22nd September 2020) - Zhang, Shang; Sunindijo, Riza Yosia; Loosemore, Martin; Wang, Shejiang; Gu, Yajun; Li, Hongfei
Abstract : Purpose: The image of the construction industry in China, as in many other countries, is tarnished by its poor safety record. With the rapid development of subway systems in Chinese urban areas, construction workers are being exposed to new risks which are poorly understood and managed. Subway construction projects are large scale and scattered over many construction sites, and involve numerous stakeholders and sophisticated technologies in challenging underground environments. Accident rates are high and have significant economic and social consequences for the firms and people involved. Addressing the gap in research about the safety risk in these projects, the purpose of this paper is to advance understanding of the factors influencing the safety of Chinese subway construction projects with the overall objective of reducing accident rates. Design/methodology/approach: A survey was conducted with 399 subway construction professionals across five stakeholder groups. Follow-up interviews were also conducted with five experienced experts in safety management on subway projects to validate the results. Findings: It was found that the eight most critical factors perceived by stakeholders to influence safety risks on Chinese subway projects are: project management team; contractor-related factors; site underground environment; safety protection during the use of machines; safety management investment; site construction monitoring and measurement; hazard identification and communication; and use of machines in all stages. This indicates that in allocating limited project resources to improve the safety of subway projects, managers should focus on: developing safety knowledge and positive attitudes in leadership teams; formulating effective risk management systems to identify, assess, mitigate, measure and monitor safety risks on site; improving communications with stakeholders about these risks and effectively managing plant, equipment and machinery. Originality/value: This research contributes a new multi-stakeholder perspective to the lack of safety research in Chinese subway construction projects. The research findings provide important new insights for policymakers and managers in improving safety outcomes on these major projects, producing potentially significant social and economic benefits for society and the construction industry.